Genetic diversity of multidrug-resistant tuberculosis in a resource-limited region of China - Dan Zhang (International Journal of Infectious Diseases, 2014)
Objectives: To gain an insight into the genetic diversity of multidrug-resistant (MDR) Mycobacterium tuberculosis isolates in Chongqing Municipality, an MDR tuberculosis (MDR-TB) epidemic region of China. Methods: In this study, a total of 208 M. tuberculosis isolates from smear-positive TB patients in Chongqing were genotyped by spoligotyping and mycobacterial interspersed repetitive unit–variable number tandem repeat typing (MIRU-VNTR). In addition, statistical analysis was performed to evaluate the distributions of drug susceptibility patterns and demographic data among different genotypes. Results: Our results showed that 156 MDR M. tuberculosis strains (75.0%) belonged to the Beijing genotype, while the other 52 strains (25.0%) were non-Beijing genotype. The proportion of Beijing genotype in the re-treated patient group was significantly higher than that in the new patient group (p = 0.013), while drug resistance and demographic characteristics showed no statistically significant associations with Beijing genotype (p > 0.05). In addition, the 208 strains were clustered into 193 genotypes using a 10-locus VNTR set; the cumulative clustering rate was 12.98% and the HGDI was 0.9991. Conclusions: Beijing genotype was the predominant genotype among the isolates from MDR-TB cases in Chongqing. The re-treated MDR-TB cases were more likely to be attributed to Beijing genotype infection. The 10-locus VNTR set demonstrated a good discrimination power for genotyping MDR M. tuberculosis isolates circulating in Chongqing Municipality.